7 Years later: Some Thoughts on the Developing of Qualification Framework - O. V. Budzinskaya; V. S. Sheinbaum (Высшее образование в России)
The article addresses the problem of combining the emerging country’s new regulatory framework in the field of qualifications, based on professional standards, with the international standards of the Association “WorldSkills International” and corporate standards used in the development and evaluation of personnel, based on the competence approach. The authors focus on the proposals to overcome the differences in the conceptual apparatus relating to a term “qualification”, which is interpreted differently in academic and business communities. The article discusses the possibilities of fixing the qualifications of employees directly in the professional standards that determine the requirements for them. Today there are three approaches that are applied to unite and standardize qualification requirements. The issue is to harmonize them in order to create the national qualification system where the key terms – “expertise”, “competency” and “qualification” are properly aligned.